Environmental education: the challenge of constructing a critical, complex and reflective thinking (Educação e Pesquisa, 2005)
The proliferation of risks, particularly of those of severe environmental and technological consequences, is a key element to understand the features, limitations and transformations of our modernity. The complexity of this process is more and more clear in a society not only increasingly threatened but also increasingly affected by socio-environmental risks and harms. The contemporary risks expose the limits and consequences of social practices, bringing with them a new element: the "reflectiveness". The society, a producer of risks, becomes more and more reflective, which means that it becomes a theme and a problem to itself. The concept of risk assumes a strategic role in understanding the characteristics, limitations, and transformations of the historical project of modernity, and to reorient collective and individual lifestyles. In a context marked by the continual degradation of the environment and of its ecosystem, this involves an array of actors from the educative universe in all its levels, stimulating the involvement of the various systems of knowledge and their formation in an interdisciplinary perspective. Educators play a strategic and decisive role in the insertion of environmental education in school everyday life, preparing their students for a critical attitude before the socio-environmental crisis, having as their horizon the transformation of social habits and practices, and the constitution of an environmental citizenship that will motivate them to the issue of sustainability in its wider meaning.